Pengaruh Persepsi Pembelajaran Housekeeping Terhadap Pemilihan Karir Bagi Siswa SMKN 3 Bogor - Taviprawati, Ervina; Sembiring, Vienna Artina; Tarigan, Emenina (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2020)
SMKN 3 is the only State Vocational School that has the competence of Hospitality Accommodation expertise in the city of Bogor. Hospitality Accommodation expertise competencies focus on vocational hospitality in particular hotel room division. So that the target of hospitality accommodation graduates can be a competent workforce in the Front Office or Housekeeping department in the hotel. But over time, the competency of hospitality accommodation expertise at SMKN 3 Bogor has become increasingly popular but is not the first choice for career selection after graduation, especially in housekeeping learning. In this study, using a descriptive method with a quantitative approach. The population is students from SMK Negeri 3 Bogor in particular are 85 students in the Hospitality Accommodation Expertise Competency. The study was conducted in April - July 2015, with the distribution of questionnaire questionnaires on May 25-27 2015 located at SMK Negeri 3 Bogor which is located at Jalan Raya Pajajaran No. 84 RT 05/06, Babakan, North Bogor, West Java. The results of the study are students who study Housekeeping in their schools and have the motivation to learn Housekeeping in their schools greatly affect the lives of these students every day. Students who choose a career in the field of Housekeeping because according to their personality can help these students interact with many people. Keywords : Learning Perception; Students; Vocational High School; Housekeeping